(untitled) (Research, Society and Development, 2020)
Objective: to identify in the scientific studies of nursing the work process that constitutes the practice of nurses in occupational health. Methodology: integrative literature review carried out in the MEDLINE, LILACS, BDENF and IBECS databases. For the search, the descriptors of worker health, nursing and work were used. The inclusion criteria established were: complete articles; published in the last five years, languages Portuguese, English and Spanish; main subject nursing at work and; free access. Exclusion criteria were: literature reviews, articles that did not address actions directed at workers’ health and did not present nursing participation in these actions. Results: the universe of this review of 28 articles was organized in a synoptic table in three categories: Work process of nurses in the management of occupational health; Nurses ’work process in the area of promotion and protection of workers’ health and; Nurses’ work process in health care for workers. Conclusion: the work process of nurses in workers ’health is characterized by a diversified action that includes management, promotion, protection and assistance to workers’ health. To act aimed at providing comprehensive care and with a view to health production.